Establishment of Childhood's Discipline Characters in a Clean and Healthy Life Behavior in The Pandemic Covid-19 - Pahenra, Pahenra; Hermanto, Hermanto; Amalia, Waode Sari; Idhayani, Nurul; Salma, Siti (Jurnal Pendidikan Indonesia, 2022)
Clean and healthy living behavior is a big challenge in early childhood education, especially during the Clean and healthy living behavior is a big challenge in early childhood education, especially during the covid 19 pandemic. One of the primary keys, in this case, is the disciplined character of children. This study aims to analyze the character of children's discipline in implementing Clean and Healthy Life Behavior during the Covid-19 Pandemic. This research is a type of qualitative research with a descriptive approach. Data analysis was carried out by systematically analyzing data obtained from interviews, field notes, and other materials so that they were quickly accessible and informed to others. The results showed that children's discipline in implementing Clean and Healthy Behavior (PHBS) during the Covid-19 pandemic was optimal. It showed the character of the following actions: using masks or face shields, hand washing discipline, and discipline in the application. From social distancing, discipline in activities, discipline in consuming healthy food, and discipline in maintaining environmental cleanliness. Then the factors that influence the disciplined character of children in implementing clean and healthy living behavior during the Covid-19 pandemic consist of internal factors in the form of habits and heredity and external factors in the form of education and environmental factors.